Feasibility of a break-in period of less than 24 hours for urgent start peritoneal dialysis: a multicenter study. Issue 1 (31st December 2022) - Wen, Xi; Yang, Liming; Sun, Zhanshan; Zhang, Xiaoxuan; Zhu, Xueyan; Zhou, Wenhua; Hu, Xiaoqing; Liu, Shichen; Luo, Ping; Cui, Wenpeng
Abstract: Purpose: Urgent start peritoneal dialysis (USPD) is an effective therapeutic method for end-stage renal disease (ESRD). However, whether it is safe to initiate peritoneal dialysis (PD) within 24 h unclear. We examined the short-term outcomes of a break-in period (BI) of 24 h for patients undergoing USPD. Methods: This real-world, multicenter, retrospective cohort study evaluated USPD patients from five centers from January 2013 to August 2020. Patients were divided into BI ≤ 24 h or BI > 24 h groups. The Primary outcomes included incidence of mechanical and infectious complications. The secondary outcome was technique failure. Moreover, we presented a subgroup analysis for patients who did not receive temporary hemodialysis (HD). Results: A total of 871 USPD patients were included: 470 in the BI ≤ 24 h and 401 in the BI > 24 h groups. Mechanical and infectious complications did not differ between the two groups across the follow-up timepoints (2 weeks, 1 month, 3 months, and 6 months) ( p  > 0.05). Multiple logistic regression analysis revealed that BI ≤ 24 h was not an independent risk factor for mechanical complications, catheter migration, or infectious complications ( p  > 0.05). A BI ≤ 24 h was not an independent significant risk factor for technique failure by multivariate Cox regression analysis ( p  > 0.05). The subgroup analysis of patients who did not receive temporary HD returned the same results. Conclusion: Initiating PD within 24 h of catheter insertion was not associated with increased mechanical complications, infectious complications, or technique failures.